2006
DOI: 10.1038/sj.jes.7500495
|View full text |Cite
|
Sign up to set email alerts
|

Maternal contamination with PCBs and reproductive outcomes in an Australian population

Abstract: Polychlorinated biphenyls used previously in industry are widespread environmental contaminants under scrutiny for their possible reproductive effects in humans. In this study, 200 breast milk samples from eligible Victorian mothers were used for measuring maternal contamination and their possible effect on the offspring was investigated. No significant association was found between maternal PCB contamination and low birth weight, small for gestational age and previous miscarriage or stillbirth. The elevated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 27 publications
3
10
1
Order By: Relevance
“…Other studies have found no relationship between maternal exposure to halogenated organics and birth weight or gestational age (Longnecker et al, 2005;Khanjani and Sim, 2006). We did not observe a consistent association between maternal exposure to PBB and infant birth weight or gestational age in this cohort.…”
Section: Discussioncontrasting
confidence: 53%
“…Other studies have found no relationship between maternal exposure to halogenated organics and birth weight or gestational age (Longnecker et al, 2005;Khanjani and Sim, 2006). We did not observe a consistent association between maternal exposure to PBB and infant birth weight or gestational age in this cohort.…”
Section: Discussioncontrasting
confidence: 53%
“…In accordance with our results, a previous study also found tendencies towards increased secondary sex ratio at higher maternal PCB exposure, although these findings were not statistically significant [43]. Accordingly, a recent review concluded that there is no convincing evidence of an association between ΣPCB and secondary sex ratio [44], although some of the studies included in the review did report a significantly decreased sex ratio at increased PCB exposure [5,6].…”
Section: Discussionsupporting
confidence: 88%
“…Related human/clinical work examines a host of social behaviors in different settings such as the home or school environment [30,31]. Other social-related research has focused on the effects of PCBs on reproductive behavior and fertility [32,33]. One of the recent reports on social behavior described the effects of PCBs on social play interactions in children in a Dutch cohort [34].…”
Section: Introductionmentioning
confidence: 99%